Screening and confirmatory tests for esbl producing organisms (escherichia coli and klebsiella species) and their genetic diversity through pcr technique - Subedi,Surya (2012)
SUMMARY: Out of the 580 urine samples processed 89 of the cases were E. coli and Klebsiella sps. Among them 77 were E. coli, 10 were Klebsiella pneumonia and 2 were Klebsiella oxytoca. 86.5% among positive cases were caused by E. coli and found to be 96.1% MDR. Among 89 positive cases 11.23 % was Klebsiella pneumonia and 90% MDR. 2.24% among positive samples was K. oxytoca and found to be 100% MDR. In urine 70.78% of organisms are ESBL positive. Most effective drug was Gentamycin, Amakicin, and Imipenem. In pus and sputum among 221 samples 17 were E. coli and Klebsiella sps. 9 samples were E. coli, 7 were Klebsiella pneumonia and one was Klebsiella oxytoca. All organisms isolated were MDR among which 52.9% were ESBL positive. One isolates was total drug resistant. No one single drug was found effective. Gentamycin, Amakicin and Imipenem were found to be effective comparatively. Keywords : E.coli, Klebsiella, MDR, ESBL